Sunshine hours and utilization of benzodiazepines - Marković Srđan Z.; Nakarada Đura J.; Mojović Miloš D.; Beljić Mirjana M.; Vuković Mira H.; Kastratović Dragana A. (Srpsko lekarsko drustvo, 2021)
Introduction: Benzodiazepines belong to the group of anxiolytic sedatives and the most prescribed drugs in the world. The authors conducted this pilot study based n large number of patients reports that they were less anxious and felt better overall by migrating to sunnier environments. Aim: We estimated the impact of the total sunshine hours per month on daily exposure of the population to Benzodiazepine anxiolytic on a monthly basis in the Republic of Serbia. Material and Methods: We conducted a retrospective academic IV phase study, which tested the correlation of time series of monthly sold Benzodiazepine anxiolytics in pharmacies and total sunshine hours per month in the Republic of Serbia, from January 2014 to May 2019. Results: According to the seasons, we did not find any difference in the increase of the population exposure to benzodiazepines. A difference was found between bromazepam consumption compared to cumulative monthly. Bromazepam consumption was negatively correlated with the cumulative monthly sunshine hours. The cutoff value for bromazepam was 131.45 cumulative monthly sunshine hours. Conclusion: This is the first pharmaco-epidemiologic study to prove that the population's exposure to benzodiazepines, in addition to the implicit health and economic effects on physicians' prescribing habits for these drugs, can be independently linked to the cumulative effects of monthly sunshine hours on the population. No difference in Benzodiazepine consumption was found in relation to the seasons (spring/summer vs autumn/winter). In months where sunshine hours was ≥135.45, the need for bromazepam was significantly reduced. Seasonal variation of climatic effects of total monthly sunshine hours is significantly correlated with the population's need for benzodiazepines with anxiolytic effects longer than 12 hours.